2010
DOI: 10.4141/cjss09030
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved soil organic carbon and nitrogen were affected by conversion of native forests to plantations in subtropical China

Abstract: . 2010. Dissolved soil organic carbon and nitrogen were affected by conversion of native forests to plantations in subtropical China. Can. J. Soil Sci. 90: 27Á36. To better understand the impact of converting native forests to intensively managed plantations on soil carbon (C) and nitrogen (N) dynamics in subtropical China, we examined the seasonal patterns of water-soluble organic C (WSOC) and N (WSON) concentrations in soils in Chinese chestnut (Castanea mollissima Blume) (CF) and bamboo (Phyllostachys praec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 40 publications
3
16
1
2
Order By: Relevance
“…It is known that the concentrations of DOC and DON are mainly derived from ground litter, root exudates, soil humus, soil microbial biomass, and rainfall leaching [26]. Wu et al [27] found that excessive consumption by microbial populations would decrease the DOC and DON in seasons with high temperature and high precipitation, which is consistent with our result. DOC and DON are important carriers of C and N loss in forest soil [28,29].…”
Section: Effects Of Management Practices On Soil Doc and Donsupporting
confidence: 91%
See 1 more Smart Citation
“…It is known that the concentrations of DOC and DON are mainly derived from ground litter, root exudates, soil humus, soil microbial biomass, and rainfall leaching [26]. Wu et al [27] found that excessive consumption by microbial populations would decrease the DOC and DON in seasons with high temperature and high precipitation, which is consistent with our result. DOC and DON are important carriers of C and N loss in forest soil [28,29].…”
Section: Effects Of Management Practices On Soil Doc and Donsupporting
confidence: 91%
“…Our previous study on this site showed that IM significantly increased soil MBC [21], indicating an increase in DOC consumption, which might greatly contribute to lower DOC concentrations in the IM plots than in the CM plots. Changed nutrient dynamics caused by management practices can also affect DOM concentrations between the native forests and plantations [27]. Long-term fertilization in the IM plots induced the loss of soil organic C and N and greatly decreased the chemical activity of the soil [20].…”
Section: Effects Of Management Practices On Soil Doc and Donmentioning
confidence: 99%
“…It is distributed from low-to high-mountain regions at approximately 1800 m above sea level (a.s.l.). Management practices for increasing bamboo production, including regular removal of understory vegetation, tillage, and fertilizer application, can increase the soil CO 2 efflux (Liu et al, 2011) and watersoluble organic N concentration (Wu et al, 2010). However, these management practices can lower the microbial functional diversity (Xu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the soil organic carbon, decomposition increases the relative abundance of alkyl C [49,50], which in turn increases the proportion of hydrophobic C [51,52]. A high proportion of aliphatic C indicates simpler molecular structures that are more readily decomposed, whereas a high proportion of aromatic C contents indicates complicated structures that are more resistant to decomposition.…”
Section: Effects Of Intensive Management On Soil Organic Carbon Pool mentioning
confidence: 99%